(untitled) (Research, Society and Development, 2024)
This study aimed to evaluate weaning at 10 days of age and use of milk replacer, considering that the control group was conventional weaning at 21 days. Two hundred eighty-eight animals were used, and birth weights at 10, 21, 66, and 163 days of age were evaluated. At the slaughterhouse, measurements were taken of hot carcass weight, backfat and muscle thickness, and percentage of lean meat. There was no statistical difference in weight at birth and at 10 days. From 21 days of age onwards, there was a difference in all measures of animal weight and weight gain, with the averages for control animals being higher when compared with the treatment. Regarding measurements at the slaughterhouse, there was a statistical difference in relation to muscle depth and carcass weight, and animals in the control group showed better results when compared with treatment. We concluded that piglets weaned at 21 days of age have greater growth potential, as maximizing weaning weight is a key point in pig production.